Surgical Management of Congenital TEV in Children at PMC Hospital Nawabshah - Saeed Samo; Zulfiqar Soomro; Zamir Soomro; Mehtab Pirwani (Journal of Basic & Applied Sciences, 2012)
Introduction: Talipes equino varus TEV is one of the most common congenital anomaly. It is managed by some common ways i-e., conservative & surgical methods. Among surgical methods are Turco’s posterior medial release, posterior soft tissue release operation (Attenborough), four quadrant release (Mc Kay). Objective of this study was to determine the reliability of surgical option like postero medial release in children having congenital TEV. Material & Methods: This study was carried out during the period from October 2002 to March 2005 in the Deptt. of Orthopaedics of PMCH Nawab Shah. The inclusion criteria were children 2 months to 30 months of age having moderate to severe club foot. Clubfoot secondary to some other disorder such as cerebral palsy, arthrogryposis multiplex congenital, myeldysplasia or DDH were not included in this study. The deformity was treated surgically in all cases by postero medial release. Follow-up period was one & half year. Results: A total 57 patients were included in this study with the age range of 2 months-2.5 yrs with moderate to severe deformity. Forty two were male (73.7%) and 15 patients (26.3%) were female, seventeen patients (29.8%) had bilateral club foot while the rest the rest of 40 patients (67.1%) had unilateral deformity. Positive family history of club foot was in 10 patients (17.5%). Results were concluded on 57 patients who completed one & half year follow-up. Excellent results were observed in 41 patients (71.9%), good in 11 patients (19.2%), fair in 2 children (3.5%). No patients lost to follow up. Conclusion: Children up to 30 months (2 months - 2.5 years) age with congenital TEV can be treated with surgery successfully.